Development of the Strategy of Information Communication Technology - Pańkowska, Małgorzata (Rozwój strategii informatyzacji, 2010)
The introduction of Information and Communication Technology (ICT) accelerates the transformation of a business organization and its methods of operation. However, provision of information or services requires consideration and preparation of a strategic plan. Although the business organizations as well as governmental institutions have formulated business strategy, they still have difficulties with constructing and implementing ICT strategy. Discussions on the functional strategies are mostly undertaken by the business strategy specialists, therefore the practitioners do not have good patterns to follow. In the paper theoretical approaches to ICT strategy formulations are delivered and analysis of six case studies is presented to visualize the practical solutions of ICT strategy development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 218-231
Keywords: business strategy; ICT strategy; governmental institutions; IT portfolio